The use of digital whiteboard in online learning / Nor Aini Hassanuddin, Sakinah Mat Zin and Noraini Ahmad - Hassanuddin, Nor Aini; Mat Zin, Sakinah; Ahmad, Noraini (Universiti Teknologi MARA, Perlis, 2023)
The traditional teaching technique of Business Mathematics mostly involves an extensive step-by-step explanation for solving any given problem. But during online classes, the main limitation is students may only listen to the lengthy explanation alone, without having chance to physically view the detailed steps. This may cause students to be less attentive, easily become bored, and subsequently lessen their interest in the subject. Due to this, some students decide not to attend the online classes for this subject or they possibly may leave in the middle of the lessons. To comply with this matter, a Digital Whiteboard has been integrated into the synchronized learning sessions. The use of Interactive Whiteboards has been widely regarded as one of the most ground-breaking teaching applications for a wide range of educational levels. It provides more effective learning where the students may view all the calculation steps on the whiteboard, as they are in the class, only it is done virtually. It also gives more chances of engagement between students and teachers. Microsoft Whiteboard is a popular application among educators that may be used as an exceptionally adaptable interactive whiteboard. The purpose of this research is to investigate students' perceptions of the usage of the Microsoft Whiteboard in the teaching and learning process. 72 students of UiTM Terengganu, from the Diploma of Muamalat (Part 2), taking Business Mathematics subject, were selected as the research sample. A 22-item online survey was used as the quantitative technique for data collection. Descriptive analysis was carried out to gauge the student’s perception of the application of Microsoft Whiteboard. The findings showed positive results on students’ perception, participation, and emotion, indicating high acceptance towards the application of Microsoft Whiteboard among students. Majority of students agreed that the usage of Microsoft Whiteboard has aided them to comprehend the materials conveyed during online in a better way. The use of a digital whiteboard can attract and supports students’ participation, thus may improve their understanding while learning. Thus, the use of the Microsoft Whiteboard application as one of the online pedagogies for the educators is highly encouraged.